2019
DOI: 10.1177/0002716219856878
|View full text |Cite
|
Sign up to set email alerts
|

Mexican Migrant Integration in the United States, 1965–2015

Abstract: This article uses 20 years of survey data from the Mexican Migration Project to describe how the experiences of Mexico-U.S. migrants have changed over time. I use survey questions about migrants’ experiences on their last U.S. trip to develop composite indices of six integration domains, and then estimate random intercept linear regression models with individual-, family-, and community-level characteristics to explain variations in Mexican migrant integration. I find that, over time, Mexican migrant linguisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Finally, as an additional indicator of social connectedness in the host country, language acquisition is operationally defined as a migrant's ability to speak and understand English or usage of English across a range of distinct social contexts. Language acquisition is an important component of occupational and spatial mobility and expands migrants' access to a range of institutions and associations in the host country (Tienda and Neidert 1984;Logan, Alba and Zhang 2002;Albarracín 2016;Lindstrom 2019). These outcome variables, along with covariates, are described in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, as an additional indicator of social connectedness in the host country, language acquisition is operationally defined as a migrant's ability to speak and understand English or usage of English across a range of distinct social contexts. Language acquisition is an important component of occupational and spatial mobility and expands migrants' access to a range of institutions and associations in the host country (Tienda and Neidert 1984;Logan, Alba and Zhang 2002;Albarracín 2016;Lindstrom 2019). These outcome variables, along with covariates, are described in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Research on migrants' employment patterns has also shown that undocumented migrants are more likely than documented migrants to be channeled away from the formal sector and into the secondary labor market, where they face unstable employment and systematically lower wages (Durand, Massey and Pren 2016;Lindstrom 2019). In addition, the social isolation that stems from being undocumented is well-established (Chavez 1991;Harrison and Lloyd 2012;Albarracín 2016;Schachter 2016;Leyro 2018;Lindstrom 2019). Research on neighbor preferences has identified a strong bias against undocumented people, the magnitude of which is comparable to the bias against people marked with a criminal record (Schachter 2016).…”
Section: Hypothesesmentioning
confidence: 99%
“…Second, naturalization may bring immigrants more privileged socioeconomic resources, such as higher income per job and more favorable leave policies. With these privileges, naturalized immigrants can adjust work schedules more flexibly and win more time for childcare, compared to non-naturalized immigrant parents (Bianchi et al 2004;Bratsberg, Ragan, and Nasir 2002;Catron 2019;Lindstrom 2019).…”
Section: Theory Of Immigrant Integration and Assimilationmentioning
confidence: 99%
“…That said, the weakened cohesion between immigrant parents and their children may reduce naturalized immigrants' parental time spent with their children, and the reasons vary. For example, naturalized parents may be more accustomed to the host country language and spend less parental time teaching children their home language, compared to newly arriving, non-naturalized parents who may spend more time speaking their home language and training children to speak their home language as well (Lee and Zhou 2004;Lindstrom 2019;Portes and Rumbaut 2001;White and Glick 2000). Newly arriving parents' knowledge of children's whereabouts and the number of times parents monitor schoolwork have outperformed native-born parents and parents who have resided longer in the U.S. (Glick and White 2004;White and Glick 2000).…”
Section: Theory Of Family Cohesionmentioning
confidence: 99%
“…The paper makes three important contributions to the literature. First, most research on migrants' integration studies international immigration in Europe and North America and emphasizes immigrants' economic, social and cultural integration (Constant & Shachmurove, 2006; Hainmueller et al, 2017; Hopp & Martin, 2017; Lindstrom, 2019; Lofstrom, 2013). Our paper focuses on domestic migrants in the non‐Western context of China, the number of which has increased dramatically due to the current Hu‐Kou reform and rapid urbanization.…”
Section: Introductionmentioning
confidence: 99%